Performance Analysis Of DSDV, AOMDV and ZRP Routing Protocols Application Simulation In Pekanbaru Vehicular Ad Hoc Network (VANET) - Ery Safrianti; Linna Oktaviana Sari; Fitriani Saputri (Centre for Research and Development on Resources, Equipment, and Operations of Posts and I, 2020)
The increase in the number of vehicles without the development of driving safety technology, tends to create adverse impacts on society, such as a rise in casualties due to road accidents. Therefore, vehicles need information on the condition of the surrounding traffic environment to provide driver with safety. One of the methods used to obtain prompt information between vehicles that move dynamically is communication technology such as Vehicular Ad hoc Network (VANET). VANET has network characteristics that change rapidly due to the highly dynamic node movement. Therefore, it is necessary to choose the right routing protocol for optimal data transmission. In this study, the DSDV (Destination Sequenced Distance Vector), AOMDV (Ad-hoc on Demand Multipath Distance Vector), and ZRP (Zone Routing Protocol) routing protocols were tested using 3 field data scenarios. The first scenario is a variation of the number of nodes 100, 250, 600, and 700 nodes. The second scenario is a variation of the transmission ranges of 250m, 500m, and 1km. The third scenario is the variation of node speeds of 10 km/hour, 20 km/hour, 30 km/hour, 40 km/hour, and 50 km/hour in Pekanbaru city of Riau province. This research was carried out using the simulation method along with the QoS (Quality of Service) performance testing parameters comprising packet delivery ratio, end to end delay, throughput, collision rate, and packet loss. Out of the three scenarios tested, AOMDV is the best routing protocol to be implemented because it outperforms the other two protocol evaluated in all designated scenarios in the paper. Meanwhile, DSDV and ZRP are superior in end to end delay and routing overhead parameters, respectively.